Synthesis and Evaluation of Novel 5-Arylidene-2-(7-chloroquinolin-6-yl)-3-(pyrimidin-2-yl) Thiazolidin-4-Ones as Anti-Microbial Agents - Pritam N. Dube; Yogita B. Thombare (Chemistry Proceedings)
The development of combination chemotherapeutic drugs, each with distinct mechanisms and minimal side effects, is crucial in combating antimicrobial resistance. Discovering novel drugs with diverse mechanisms is laborious and time-consuming. Alternatively, combining multiple pharmacophores into a single molecule offers a promising strategy to develop more effective treatments. In this study, we synthesized and assessed the antimicrobial activity of novel 5-arylidene-2-(7-chloroquinolin-6-yl)-3-(pyrimidin-2-yl) thiazolidin-4-ones.